Gravity effect on thermal-solutal convection during solidification revealed by four-dimensional synchrotron imaging with compositional mapping. (15th April 2020) - Nelson, T.; Cai, B.; Warnken, N.; Lee, P.D.; Boller, E.; Magdysyuk, O.V.; Green, N.R.
Abstract: The effect of gravity on thermo-solutal convection and its impact on solidification dynamics of an Al-15 wt%Cu alloy were studied using high speed synchrotron tomography. A method for mapping the composition of the solidifying samples was developed, enabling three-dimensional quantification of the time evolved solute concentration and dendrite morphology. Differences in solute segregation, dendrite morphology and fragmentation between upwards and downwards solidification were identified, which were attributed to buoyancy-modulated thermal-solutal convection. Graphical abstract: Image, graphical abstract